Between hope and weight: Psychological experiences of women with obesity facing preoperative weight-loss requirements for breast reconstruction—A qualitative thematic analysis - Iris L. Holt-Kedde; Ceciel H. C. Houtsma; Maya J. Schroevers; Marlous Arjaans; Grieteke Pool (Journal of Health Psychology, 2026)
This qualitative study explored the psychological experiences of Dutch women with obesity who were required to lose weight before delayed breast-reconstruction following mastectomy. Fourteen Dutch women participated in semi-structured interviews, which were analyzed using thematic analysis. Three interconnected themes emerged: coping with stress, interpersonal and healthcare experiences, and the interplay between coping and interpersonal experiences. Women who described trusting and supportive interactions generally reported greater self-efficacy, more effective stress management, and more constructive communication with healthcare professionals. In contrast, women reporting interpersonal difficulties often described challenges with emotion regulation, long-standing weight-management struggles and coping with delayed reconstruction. Across participants, BMI-based eligibility criteria were experienced as a major psychosocial stressor. These findings suggest that preoperative weight-loss requirements may have substantial psychological consequences for women awaiting breast reconstruction. Personalized psychosocial support and sensitive physician communication may strengthen coping capacities, particularly among women experiencing stress-regulation difficulties and interpersonal challenges.